"First in first out" or "last in first out": Presentation of information order on evaluation of utilitarian products. (May 2017) - Tingchi Liu, Matthew; Phau, Ian; Teah, Min
Abstract: This study investigates how the presentation order of information may affect the evaluation of utilitarian products. Three experiments with different conditions (hedonic/utilitarian product; experience/search advertisement; unattractive/attractive packaging) were conducted with a total of 334 participants in Macau. This study tests both the affective and cognitive product evaluation. The findings indicate that assimilation effect occurs if the search advertisement of a utilitarian product is presented before and if the consumers have better cognitive evaluation. When an experience advertisement is presented before, contrast effect occurs and affective evaluation is reduced. However, when unattractive packaging is presented before, assimilation effect occurs, and cognitive evaluation is increased. When attractive packaging is presented before, the consumers demonstrate a positive cognitive and affective evaluation for the utilitarian product. These findings contribute to a better understanding of the role of presentation order on the consumers' evaluation of utilitarian products from theoretical and managerial perspectives. Highlights: This paper contributes to a better understanding of the role of assimilation effect on evaluation of consumer products leading to purchase decision. This has implications for effects related to the order of presentation of information to the consumers and will help resolve apparent inconsistencies in prior research on order effects in the context of choices for sequentially utilitarian products.